A health risk assessment of Arabian incense (Bakhour) smoke in the United Arab Emirates - Dalibalta, Sarah (2015)
Burning Arabian incense (Bakhour) is a common practice in the Middle East and Arabian Gulf. Although the incense generates large amounts of chemicals and air pollutants, little is known with regard to the nature of these chemicals and their potential health risks. The aim of this study is to provide a comprehensive characterization of the chemical constituents emitted in Bakhour smoke, and subsequently to examine the associated health implications of these components. Thermo-gravimetric analysis was used to investigate the presence and the thermal profile of volatile organic compounds in three different samples of Bakhour smoke. Thermal desorption-gas chromatography-mass spectrometry was then applied to isolate all the volatile and semi-volatile compounds present in the Bakhour smoke samples. Using a spectral library and an extensive literature search, all organic compounds detected were analyzed for potential health risks. A total of 859 compounds were emitted from burning the different Bakhour samples. The novel finding of this research shows that 42 detected compounds are suspected/known carcinogens, 20 are known to have toxic effects, and at least 200 compounds are known irritants to the eyes, skin, respiratory and digestive tracts, as reported in human and/or animal studies. Our study suggests that inhaled Bakhour smoke contains a substantial number of adverse compounds, which are known to be detrimental to human health. Moreover, the evidence presented shows that incense burning is a significant source of environmental pollution; with the potential of significant health concerns particularly with long term exposure. As the majority of the compounds detected have no reported clinical data, there is an urgent need for significant research in this field.